Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Melatonin alleviates chilling injury in postharvest banana fruit by modulating membrane lipid and phenolic metabolism - Jing Lin; Rui Zhang; Qi Chen; Weiqi Liang; Yanting Wu; Wenbing Su; Wei Wei; Hetong Lin; Zhongqi Fan (Postharvest Biology and Technology, 2026)

Rhodamine B degradation through sulfite activation by Vernadite: Kinetics characteristics and reaction mechanism - Wenteng Chu; Runshen Feng; Cheng Wang; Yanting Pan; Hong Su; Feng Jiang; Xiaoming Wang; Hui Yin; Xionghan Feng (Applied Geochemistry, 2026)

Preparation and characterization of chitosan‑sodium alginate complex edible casings incorporated with tea polyphenols and their application in dry-cured sausages - Huanhuan Li; Yanting Gao; Teng Xu; Ke Zhao; Mingwei Su; Jun He; Honggang Tang (Food Chemistry, 2026)

Inorganic Arsenic Attenuates Crystalline Silica-Induced Pulmonary Inflammation and Fibrosis by Ameliorating Autophagolysosomal Dysfunction in Alveolar Macrophages - Yi Luo; Wei Su; Yong Luo; Yanting Han; Shuwen Gong; Fuhai Shen; Yulan Jin; Yi Guan; Xinyuan Zhao; Jinlong Li (Biological Trace Element Research, 2026)

Exploring the mechanisms of torularhodin in alleviating diabetic kidney disease: a microbiome and metabolomics approach through the gut-kidney axis - Wenlong Deng; Yi Guo; Qigui Mo; Jiaqi Liu; Yanting Su; Zhihao Wei; Runtao Ma; Jiaqi Chen; Yue Song; Tianqi Chen; Peng Wang; Wei Yu; et al. (Food Research International, 2025)

The process of trace metals enrichment in pyrite under methane seepage in the northern South China Sea - Yanting Ling; Xuan Chen; Daidai Wu; Qinyi Zhang; Shengyi Mao; Guangrong Jin; Jie Liu; Haizhen Zhai; Chao Yang; Zheng Su; Nengyou Wu (Frontiers in Marine Science, 2025)
Pyrite is an important indicator of methane seepage. The effects of organic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) on the trace metals in pyrite have aroused interest; however, further studies about how these two pathways control the trace element patterns are still required. Therefore, we studied the geochemical and mineralogical characteristics of sediment samples from the northern South China Sea, aiming to investigate the enrichment mechanisms of trace elements into pyrites in methane seep systems. We applied laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) to analyze the trace element patterns of pyrites in core Z22–3. We used Sr/Ca-Mg/Ca, (Mo/U) EF values, chromium reducible sulfur (CRS) content, total organic carbon (TOC), δ 34 S, and δ 13 C values of bulk sediments to determine the position of sulfate–methane transition zones (SMTZs). Progressively more positive δ 34 S values (up to −36.54‰) of the CRS and an increase in Mg/Ca indicate the enhancement of SD-AOM, suggesting that the position of SMTZs is located at depths of 181 to 481 and 1,101 to 1,401 cmbsf. Within SMTZs, pyrites exhibit obvious enrichments in Co, Ni, Mo, and Pb and depletion in Mn, Zn, Cu, and V. We discuss the process of methane seepage affecting trace elements in pyrites: the reductive dissolution of iron/manganese oxyhydroxide aggregates fueled by the enhancement of AOM and substitution for ferrous in pyrites contribute to the enrichments of Mo, Co and Ni in pyrites. Elements with faster water exchange kinetics rates than Fe, such as Cu, Pb and Zn, rather precipitate as independent metal sulfides than incorporating into pyrite, thus resulting in the depletion of these trace elements in pyrites. This study provides novel insight into the deep-sea trace element cycle between sediments and authigenic pyrites, establishing geochemical indicators of AOM based on trace element patterns in pyrites.

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Chaetoglobosin D isolated from the endophytic fungus MG2 exhibited a good control to apple tree Valsa canker - Yanting He; Xiaozhou Su; Weimin Ma; Fei Qu; Hao Feng; Lili Huang (Pesticide Biochemistry and Physiology, 2025)

Exploration into the Mechanism of Yiyi Baijiang Decoction Attenuating Chronic Pelvic Inflammation Based on Network Pharmacology and Experimental Verification - Yanting Wei; Hongning Su; Jiajia Li; Wenli Zheng; Lili Li; Miao Zhou; Yimeng Sun (Biochemical Genetics, 2025)

Enhancing the sensitivity of Co-doped LaFeO3 thick-film sensors for low-concentration CO2 detection: Investigating the synergistic effect of complex defects and adsorbed oxygen - Xiaohong Su; Haotian Shan; Yanting Tian; Wei Guo; Peng Zhao; Lin Xue; Yongjia Zhang (Journal of Environmental Chemical Engineering, 2025)

Improving the accuracy of microclimate coupled urban building energy modeling using convolutional neural networks - Jiahong Ye; Chenyu Huang; Zhengjia Zhong; Yanting Shen; Xiangyu Ao; Yunsheng Su; Jing Cao; Haipeng Duan; Jiawei Yao (Building and Environment, 2025)

The role of hydrogen sulfide in the regulation of necroptosis across various pathological processes - Shiyun Guo; Yanting Zhang; Jingwen Lian; Chunqi Su; Honggang Wang (Molecular and Cellular Biochemistry, 2025)

Biocontrol potential of the active substance isolated from the endophytic fungus Aa-Lcht against apple Valsa canker - Yanting He; Hua Wang; Weimin Ma; Chengyu Gao; Runze Tian; Xiaozhou Su; Hao Feng; Lili Huang (Pesticide Biochemistry and Physiology, 2025)

MaERF9 and MaERF113 transcription factors involve in chilling injury development by regulating membrane lipid metabolism of postharvest banana fruit - Lijuan Bai; Yanting Wu; Hetong Lin; Wenbing Su; Zhongqi Fan (Postharvest Biology and Technology, 2025)

From stem cells to pancreatic β-cells: strategies, applications, and potential treatments for diabetes - Xingrong Feng; Hongmei Zhang; Shanshan Yang; Daxin Cui; Yanting Wu; Xiaocun Qi; Zhiguang Su (Molecular and Cellular Biochemistry, 2025)

Integrated analysis of radiomics, RNA, and clinicopathologic phenotype reveals biological basis of prognostic risk stratification in colorectal cancer - Xiaobo Chen; Yanqi Huang; Leonard Wee; Ke Zhao; Yun Mao; Zhenhui Li; Su Yao; Suyun Li; Yanting Liang; Xin Huang; Andre Dekker; Xin Chen; et al. (Science Bulletin, 2024)

No-interfered and visual evaluation of global warming impacts on phytoplankton-based copper bioavailability and then carbon sequestration - Fengjiao Liu; Lingling Su; Yanting Du; Huali Li; Jiayi Luo; Xuguang Huang; Shunxing Li; Fengying Zheng (Science of The Total Environment, 2024)

Effect of auxiliary materials on the formation of humic acid carbon and nitrogen and bacterial dynamics in kitchen waste composting - Yabin Zhan; Su Chang; Yanting Chen; Yuan Chang; Peizhen Chen; Yunfeng Chen; Longli Zhang; Li Yang; Xiange Xia; Ji Li; Yuquan Wei (Journal of Environmental Chemical Engineering, 2024)

Long-term investigation of spatial–temporal variations, risk assessments, and controlling factors of persistent organic pollutants (HCHs, DDTs, and PAHs) and heavy metals in coastal regions along the Chinese Bohai Sea - Yanting Su; Wanguan Wang; Yueyue Su; Xiaoxuan Wang; Haitao Zhao; Zhunjie Li; You Yu (Frontiers in Marine Science, 2024)
Persistent organic pollutants (POPs) and heavy metals in marine systems have been given more and more attention due to their high toxicity and bioaccumulation capacity. After discharging into the marine systems, large proportions of POPs and heavy metals are likely to remain in coastal seas, causing serious contamination and high ecological risks. However, the lack of systematic studies restricts our understanding of POP and heavy metal cycling in coastal regions. Herein, the coastal regions along the Chinese Bohai Sea (an important fishing and typically polluted area) were chosen to establish a study model for investigating long-term spatial–temporal variations, risk assessments, and controlling factors of hexachlorocyclohexanes (HCHs), dichlorodiphenyltrichloroethanes (DDTs), polycyclic aromatic hydrocarbons (PAHs), and heavy metals in coastal regions. The results showed that concentrations of HCHs, DDTs, and PAHs in sediment, and contents of heavy metals in seawater and sediment were higher than those in other coastal regions during 2015–2018 and that concentrations of As and Cu in approximately 95% and 20% of sampled organisms exceeded maximum permissible levels recommended by China and the WHO, respectively. The significantly temporal variations in HCH and PAH concentrations were indicative of increasing POP pollution, and no significantly temporal variations in most heavy metal concentrations were found. Meanwhile, the higher concentrations of POPs and heavy metals were mainly located in estuaries and other nearshore areas. The geo-accumulation index (I geo ), potential ecological risk index (PERI), and provisional tolerable daily intake (PTDI) showed that As, Cd and Hg should be listed as the primary heavy metal pollutants in sediment; higher dietary risk was posed by As through seafood consumption; the dietary risks posed by HCHs, DDTs, and PAHs were lower. Finally, the results of multiple regression, Pearson’s, and cluster analyses indicated that anthropogenic activities (e.g., industrial and agricultural discharges, and riverine input) played important roles in controlling HCH, DDT, PAH, and heavy metal distributions in coastal regions along the Chinese Bohai Sea. The outcomes of this study are expected to shed new light on an improved understanding of POP and heavy metal cycling and provide a scientific basis for contamination control in coastal systems.

Metabolomics analysis of advancing humification mechanism in secondary fermentation of composting by fungal bioaugmentation - Yuyun Wang; Jun Li; Yuan Chang; Su Chang; Yanting Chen; Dan Wei; Ruoqi Li; Yi Zheng; Zitong Kang; Zhen Wu; Peizhen Chen; Yuquan Wei; et al. (Science of The Total Environment, 2024)

Identification a novel clinical biomarker in early diagnosis of human non-small cell lung cancer - Yanxia Jin; Yajun Yang; Yanting Su; Xiangdong Ye; Wei Liu; Qing Yang; Jie Wang; Xiangning Fu; Yongsheng Gong; Hui Sun (Glycoconjugate Journal, 2019)

Association between Val66Met polymorphisms in brain-derived neurotrophic factor gene and asthma risk: a meta-analysis - Xinming Xie; Yanting Zhu; Jiaojiao Zhang; Cui Zhai; Wei Feng; Yilin Pan; Lu Liu; Xiaofan Su; Lan Yang; Manxiang Li (Inflammation Research, 2015)